Diversity in Germination Behaviour and High Temperature Tolerance in the Seeds of Oorohorus Aestuans Linn. - Chawan, D D; Sen, D N (Annals of Arid Zone, 2016)
Seeds of five individual plant populations in Corchorus aestuans failed to germinate because . of an impermeable seed coat. The application of dry heat pretreatment brought forth higherÂ germination values. Seed collected from five different plant populations indicated diverse germination behaviour and high temperature tolerance.